DESEMPENHO INDUSTRIAL E PARÂMETROS GENÉTICOS DE CARACTERES DA PLANTA DE GIRASSOL - Gaviraghi, Juliano; Bandeira, Taiane P.; Cappellari, Geverson J.; Silva, Adair J. d.; Antonow, Diovane; Matter, Edegar; Mattioni, Tânia C.; Maixner, Adriano R.; Krüger, Cleusa A. M. B.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo